2017
DOI: 10.1155/2017/9170768
|View full text |Cite
|
Sign up to set email alerts
|

Drip Loss Assessment by Different Analytical Methods and Their Relationships with Pork Quality Classification

Abstract: We analyzed drip loss in pork by comparing the standard bag (DL), filter-paper wetness (FPW), and EZ-DripLoss methods by weighing the meat juice container and dabbed sample after 24 h and 48 h. Samples were classified into quality categories based on pH, color, and drip loss. The relationship between DL and FPW revealed the cut-off of 5% DL as corresponding to FPW of 139 mg; 1.89% when analyzed by weighing meat juice container or dabbed sample after 24 h; and 3.18% and 3.74% for those analyzed by weighing both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 23 publications
5
25
2
2
Order By: Relevance
“…2) in drip loss determined by different methods (EZ vs. BM) at the same point of time. The results are in agreement with Christensen (2003) and Filho et al (2017), who also noticed higher drip loss values using the BM compared to the EZ method. On the contrary, Honikel and Hamm (1994), Christensen (2003), and Otto et al (2004) Figure 2.…”
Section: Relationship Between Drip Loss Values Measured By Ez Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…2) in drip loss determined by different methods (EZ vs. BM) at the same point of time. The results are in agreement with Christensen (2003) and Filho et al (2017), who also noticed higher drip loss values using the BM compared to the EZ method. On the contrary, Honikel and Hamm (1994), Christensen (2003), and Otto et al (2004) Figure 2.…”
Section: Relationship Between Drip Loss Values Measured By Ez Methodssupporting
confidence: 90%
“…The results showed that the samples stored for 48 h had significantly higher drip loss than those stored for 24 h. Since it is known that the exudation in the muscle is a complex and slow process, this was somehow expected. Otto et al (2004), Correa et al (2007), Filho et al (2017), and Holman et al (2020) also confirmed this tendency for drip loss to increase with storage period. The difference in mean values for the EZ method in the present study between 24 and 48 h of storage was 0.28 %, whereas for the same period of time for BM it was 0.80 %.…”
Section: Relationship Between Drip Loss Values Measured By Ez Methods mentioning
confidence: 78%
“…Breast meat was used to determine postmortem pH (t = 0.5 and 24 h) by pH meter. Drip loss was estimated according to [22] (percent; proportional weight loss of a sample suspended for 72 h in a closed plastic bag under refrigerated conditions at 4 °C). After storage at −20 °C, cooking loss was determined (percent; weight loss proportionate of a sample after cooking for 40 min in a water bath at 70 °C followed by cooling).…”
Section: Methodsmentioning
confidence: 99%
“…Losses of water from meat can occur via evaporation, gravitational drip, thawing, or cooking, and low water holding capacity (Apple & Yancey, 2013). Measurement of drip loss is to determine the water holding capacity of meat (Apple & Yancey, 2013;Torres Filho et al, 2017;Warner, 2017).…”
Section: Discussionmentioning
confidence: 99%